Specific Composition of Lipid Phases Allows Retaining an Optimal Thylakoid Membrane Fluidity in Plant Response to Low-Temperature Treatment - Mazur, Radosław; Gieczewska, Katarzyna; Kowalewska, Łucja; Kuta, Anna; Proboszcz, Małgorzata; Gruszecki, Wieslaw I.; Mostowska, Agnieszka; Garstka, Maciej (Frontiers in Plant Science, 2020)
Thylakoid membranes isolated from leaves of two plant species, the chilling tolerant (CT) pea and chilling sensitive (CS) runner bean, were assessed for the composition of lipids, carotenoids as well as for the arrangement of photosynthetic complexes. The response to stress conditions was investigated in dark-chilled and subsequently photo-activated detached leaves of pea and bean. Thylakoids of both species have a similar level of monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG), but different sulfoquinovosyldiacylglycerol to phosphatidylglycerol (PG) ratio. In pea thylakoid fraction, the MGDG, DGDG and PG, have a higher double bond index (DBI), whereas bean thylakoids contain higher levels of high melting point PG. Furthermore, the lutein to the β-carotene ratio is higher in bean thylakoids. Smaller protein/lipid ratio in pea than in bean thylakoids suggests different lipid-protein interactions in both species. The differences between species are also reflected by the course of temperature-dependent plots of chlorophyll fluorescence pointing various temperatures of the lipid phase transitions of pea and bean thylakoids. Our results showed higher fluidity of the thylakoid membrane network in pea than in bean in optimal temperature conditions. Dark-chilling decreases the photochemical activity and induces significant degradation of MGDG in bean but not in pea leaves. Similarly, substantial changes in the arrangement of photosynthetic complexes with increase in LHCII phosphorylation and disturbances of the thylakoid structure take place in bean thylakoids only. Changes in the physical properties of bean thylakoids are manifested by the conversion of a three-phase temperature-dependent plot to a one-phase plot. Subsequent photo-activation of chilled bean leaves caused a partial restoration of the photochemistry and of membrane physical properties, but not of the photosynthetic complexes arrangement nor the thylakoid network structure. Summarizing, the composition of the thylakoid lipid matrix of CT pea allows retaining the optimal fluidity of its chloroplast membranes under low temperatures. In contrast, the fluidity of CS bean thylakoids is drastically changed, leading to the reorganization of the supramolecular structure of the photosynthetic complexes and finally results in structural remodeling of the CS bean thylakoid network.